Solubility and dissolution thermodynamic data of mefenamic acid crystals in different classes of Organic solvents - Abdul Mudalip, Siti Kholijah; Abu Bakar, Mohd Rushdi; Adam, Fatmawati; Jamal, Parveen (ACS Publications, 2013)

(untitled)
Different classes of solvents provide different polarity values, which influence the solubility of pharmaceutical solids. In this article, the solubility of mefenamic acid in different classes of organic solvents, including polar protic, dipolar aprotic, and apolar aprotics at a range of temperatures from (298 to 323) K are reported. It has been found that mefenamic acid shows high solubility in dipolar aprotic solvents (N,N-dimethylacetamide, N,N-dimethylformamide, ethyl acetate, and propanone), moderate solubility in polar protic solvents (ethanol and propan-2-ol), and poor solubility in apolar aprotic solvents (hexane, heptane, and cyclohexane) and water.